Health care professionals talking: Are services for young adults with type 1 diabetes fit for purpose?. Issue 1 (9th July 2019) - Harris, Margaret; James, Steven; Perry, Lin; Lowe, Julia; Dunbabin, Janet; Steinbeck, Katharine
Abstract: Introduction: The challenges of becoming a mature adult may distract young adults with type 1 diabetes from disease self‐management, increasing risks for premature morbidity and mortality. Despite the importance of young adults with type 1 diabetes engaging with preventative diabetes‐related health care services, few studies report health care professionals' experiences and perceptions of the support that is available, including during the period of transition. This study sought to determine these factors across diverse contexts in one health jurisdiction. Methods: This qualitative study was undertaken in New South Wales, Australia. Recruitment was based on a snowball sampling technique, which began with members of an established diabetes service group. Data were collected by individual semistructured interviews with 16 health care professionals, most of whom were registered nurses (75%), working at differing levels of expertise and responsibility across metropolitan and regional/rural areas. Data were analysed using thematic analyses. Results: Participants overwhelmingly recognized the time and care needed to support young adults with type 1 diabetes to prepare them for adult self‐management and to work with adult diabetes services, and the importance of youth‐friendly services. They reported shortfalls and inequitous distribution in services for these young adults. Two themes, addressing the present and future possibilities, expressed their perceptions of services for this population: working with what is available and mapping a route to better services . Conclusion: Findings identify opportunities for development in the planning and provision of specialist multidisciplinary health care support for this population. New ideas are needed for policy and practice innovation and for the infrastructure to facilitate this, to ensure that young adults with type 1 diabetes have access to consistent and coordinated diabetes health care services, particularly in nonmetropolitan settings.